Pengaruh Profitabilitas, Umur Perusahaan, Leverage dan Ukuran Perusahaan Terhadap Nilai Perusahaan : Studi Empiris Pada Perusahaan Properti dan Real Estate Yang Terdaftar Pada Bursa Efek Indonesia Periode 2019 – 2023 - Rosa Amelia; Rinny Meidiyustiani (Jurnal Mutiara Ilmu Akuntansi, 2024)
This study was conducted to analyze profitability, company age, leverage, and company size on company value. This research was conducted at property and real estate companies listed on the Indonesia Stock Exchange for the period 2019-2023. The method of determining the sample in this study using purposive sampling method with a sample of 25 property and real estate companies that met the sample criteria. This study uses multiple linear regression analysis techniques and uses the SPSS version 22.0 statistical test tool. The results of this study indicate that the variables profitability and company size have a positive effect on company value, company age has a negative effect on company value, and leverage has no effect on company value.